Nursing management of the neurogenic bladder: Evidence map of quality and recommendations from clinical practice guidelines - Yuanyuan Li; Jinhui Tian; Luying Cheng; Jing Ni; Lin Li; Jiaoyan Zhang; Liang Zhao; Jingjie Zou; Wentao Wei; Duanying Cai (International Journal of Nursing Sciences, 2025)
Objectives: This study employed evidence mapping to systematically evaluate clinical practice guidelines (CPGs) for neurogenic bladder (NB) care. We aimed to identify research trends, evidence gaps, and consensus patterns to inform evidence-based nursing practices and support the formulation of high-quality CPGs. Methods: A systematic search of electronic databases and guideline repositories was conducted, included PubMed, Web of Science, Embase, Guidelines International Network (GIN), ect. Eligible NB guidelines underwent dual-researcher screening and extraction, and methodological and recommendation quality were assessed using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) and Evaluation-Recommendations Excellence (AGREE-REX) instruments. Five researchers independently evaluated recommendation specificity, evidence grading systems, and implementation consistency. Discrepancies were resolved through consensus discussion or third-party arbitration. Results: Analysis of 19 CPGs (2006–2023) from 11 countries/regions revealed that 78.95 % (15/19) incorporated evidence grading systems and 68.42 % (13/19) specified recommendation strength. The AGREE II evaluation identified critical methodological deficiencies, with three domains scoring below the acceptable thresholds: Rigor of Development (41.70 %), Editorial Independence (43.30 %), and Applicability (30.00 %). The AGREE-REX results showed moderate performance in Clinical Applicability (55.56 %) and implantability (41.67 %) but severe gaps in Values and Preferences (25.00 %). A systematic synthesis identified 40 recommendations: 90 % (36/40) demonstrated consensus and 10 % (4/40) contradictions. These studies addressed the following six clinical themes: 1) nursing assessment, 2) manipulation-assisted voiding, 3) behavioral therapy, 4) intermittent catheterization, 5) indwelling catheterization, and 6) other therapies. Conclusions: The methodologies and recommendations of the CPGs for NB in nursing demonstrated substantial variability. Therefore, there is an urgent need to improve the quality of the NB-related CPGs. More in-depth research and timely updates are required to enhance the practical utility of CPGs and narrow the gap between CPGs and clinical practice.